2020
DOI: 10.1177/0011128720977444
|View full text |Cite
|
Sign up to set email alerts
|

A Macrolevel Study of Police Killings at the Intersection of Race, Ethnicity, and Gender

Abstract: We investigate macrolevel sources of police use of fatal force at the intersection of race, ethnicity, and gender. Focusing on 580 U.S. counties from 2013 to 2018, we build a unique dataset and analyze whether violent crime, social disorganization, and racial conflict indicators predict police killings among six victim subgroups of Black, Hispanic, and White men and women. Regression results show that violent crime—and social disorganization, albeit less consistently—is positively associated with police killin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 85 publications
4
12
0
Order By: Relevance
“…Thus, the finding is in the opposite direction than theoretically predicted. While counter to expectations, the finding is consistent with a recent study that used Mapping Police Violence data and found that more police‐involved killings occurred in the 580 largest US counties with fewer Black residents regardless of the race and gender of the citizens killed (Gaston, Fernandes & DeShay, 2020). Gaston & colleagues (2020) argued that this could reflect a racial conflict effect attributed to ‘defended neighborhoods and out of place policing’ (p.19).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, the finding is in the opposite direction than theoretically predicted. While counter to expectations, the finding is consistent with a recent study that used Mapping Police Violence data and found that more police‐involved killings occurred in the 580 largest US counties with fewer Black residents regardless of the race and gender of the citizens killed (Gaston, Fernandes & DeShay, 2020). Gaston & colleagues (2020) argued that this could reflect a racial conflict effect attributed to ‘defended neighborhoods and out of place policing’ (p.19).…”
Section: Discussionsupporting
confidence: 83%
“…In other words, Black civilians are alone in facing a greater risk of being killed by police in White “and” Hispanic communities. These findings comport with the defended neighborhoods argument as well as with a growing literature on out‐of‐place racial profiling in which Black Americans face greater police scrutiny when found in non‐Black areas (Beck, 2019; Fagan & Davies, 2000; Gaston et al., 2020, 2021; Novak & Chamlin, 2012; Rojek et al., 2012; Stewart et al., 2009).…”
Section: Resultssupporting
confidence: 74%
“…We also found that Black Americans were the only group that faced an additional elevated risk of being killed in Hispanic‐dominated jurisdictions. These results further demonstrate the racialized nature of fatal force, which appears to reflect an effort to protect White spaces, in line with conflict theories, and profile Black Americans when they are “out of place,” or found in areas that do not match their race (Beck, 2019; Fagan & Davies, 2000; Gaston et al., 2020, 2021; Novak & Chamlin, 2012; Rojek, Rosenfeld, & Decker, 2012; Stewart et al., 2009).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations